Physical-chemical properties of FM-1 reagent as a potential collector for ion flotation of lanthanoids - Yuminova, A.A.; Giniyatullina, E.A.; Karieva, L.M.; Chekanova, L.G. (KU Publ., 2022)
The physical-chemical properties of the industrial reagent “FM-1” have been investigated. These properties are necessary for evaluating its use as a collector in the processes of concentration of rare earth metal ions by ion flotation. “FM-1”, which is based on sodium salts of aminomethylenephosphonic acids, is used as a flocculant for oil production and purification of process waters from suspended particles and petroleum products. Protolytic equilibriums in aqueous solutions of the reagents were studied. The values of dissociation constants equaling pKa1 = 2.31±0.26 and pKa2 = 8.82±0.34 were determined spectrophotometrically. Surface tension of the reagent solutions at the solution-air interface was studied. The “FM-1” reagent was classified as a strong surface-active substance with the following parameters: Minimal surface tension σmin = 29 mN∙m-1, surface activity G = 0.031 N∙m2∙mol-1, critical concentration of micelle formation 1∙10–3 mol∙L-1. The regularities of the reagent’s interaction with lanthanum (III) ions were studied. A high degree of lanthanum ions’ precipitation (over 99.7 %) was observed over a rather wide interval of pH values (4.00–12.00); at this point, at pH ≥ 7.5, lanthanum hydroxide can co-precipitate. The formation of compounds in a solution with molar ratios [La]:[FM-1] = 1:1 and 1:2 was established by conductometric titration method. The findings of chemical analysis, FTIR spectroscopy and elemental analysis of the isolated precipitates suggested their structural formula. A possibility for the “FM-1” reagent to be used as a collector for the ion flotation of lanthanum (III) ions was shown.
Лантаноидтардың иондық флотациясы үшін потенциалды жинақтаушы – «ФМ-1» реагентінің физика-химиялық қасиеттері
Лантаноидтардың иондық флотациясы үшін потенциалды жинақтаушы – «ФМ-1» реагентінің физика-химиялық қасиеттері
Keywords: ion flotation; rare-earth elements; aminomethylenephosphonic acid salts; collector; physicalchemical properties; surface-active substance; lanthanum; FM-1